The Relevance of Transcription Factors in Gastric and Colorectal Cancer Stem Cells Identification and Eradication - Pádua, Diana; Figueira, Paula; Ribeiro, Inês; Almeida, Raquel; Mesquita, Patrícia (Frontiers in Cell and Developmental Biology, 2020)
Gastric and colorectal cancers have a high incidence and mortality worldwide. The presence of cancer stem cells (CSCs) within the tumor mass has been indicated as the main reason for tumor relapse, metastasis and therapy resistance, leading to poor overall survival. Thus, the elimination of CSCs became a crucial goal for cancer treatment. The identification of these cells has been performed by using cell-surface markers, a reliable approach, however it lacks specificity and usually differs among tumor type and in some cases even within the same type. In theory, the ideal CSC markers are those that are required to maintain their stemness features. The knowledge that CSCs exhibit characteristics comparable to normal stem cells that could be associated with the expression of similar transcription factors including SOX2, OCT4, NANOG, KLF4 and c-MYC, and signaling pathways such as the Wnt/β-catenin, Hedgehog (Hh), Notch and PI3K/AKT/mTOR directed the attention to the use of these similarities to identify and target CSCs in different tumor types. Several studies have demonstrated that the abnormal expression of some transcription factors and the dysregulation of signaling pathways are associated with tumorigenesis and CSC phenotype. The disclosure of common and appropriate biomarkers for CSCs will provide an incredible tool for cancer prognosis and treatment. Therefore, this review aims to gather the new insights in gastric and colorectal CSC identification specially by using transcription factors as biomarkers and divulge promising drugs that have been found and tested for targeting these cells.